Optimal deep brain stimulation sites and networks for stimulation of the fornix in Alzheimer’s disease - Ríos, Ana Sofía; Oxenford, Simón; Neudorfer, Clemens; Butenko, Konstantin; Li, Ningfei; Rajamani, Nanditha; Boutet, Alexandre; Elias, Gavin J. B.; Germann, Jurgen; Loh, Aaron; Deeb, Wissam; Wang, Fuyixue; et al. (Nature communications, 2022)
Deep brain stimulation (DBS) to the fornix is an investigational treatment for patients with mild Alzheimer’s Disease. Outcomes from randomized clinical trials have shown that cognitive function improved in some patients but deteriorated in others. This could be explained by variance in electrode placement leading to differential engagement of neural circuits. To investigate this, we performed a post-hoc analysis on a multi-center cohort of 46 patients with DBS to the fornix (NCT00658125, NCT01608061). Using normative structural and functional connectivity data, we found that stimulation of the circuit of Papez and stria terminalis robustly associated with cognitive improvement ( R = 0.53, p < 0.001). On a local level, the optimal stimulation site resided at the direct interface between these structures ( R = 0.48, p < 0.001). Finally, modulating specific distributed brain networks related to memory accounted for optimal outcomes ( R = 0.48, p < 0.001). Findings were robust to multiple cross-validation designs and may define an optimal network target that could refine DBS surgery and programming. Deep brain stimulation has been investigated as a potential treatment for cognitive impairments in Alzheimer’s disease. Here the authors carry out post hoc analysis of multi-center cohorts to investigate the anatomical and functional correlates of effective deep brain stimulation, and find that stimulating circuit of Papez, fornix and bed nucleus of the stria terminalis, and a multi-region functional network, were associated with clinical improvement.